Clinical associations between acetylcholine levels and cholinesterase activity in saliva and gingival crevicular fluid and periodontal diseases. (17th September 2018) - Apatzidou, Danae A.; Iskas, Achilleas; Konstantinidis, Antonis; Alghamdi, Abeer M.; Tumelty, Maria; Lappin, David F.; Nile, Christopher J.
Abstract: Aim: The oral mucosa possesses a non‐neuronal cholinergic system. This study aimed to determine clinical evidence for a role of cholinergic mechanisms in the pathogenesis of periodontal diseases. Materials and Methods: Fifty healthy participants, 52 patients with gingivitis and 49 with periodontitis were recruited. Full periodontal parameters were recorded and saliva and gingival crevicular fluid (GCF) collected. Levels of acetylcholine and inflammatory mediators were quantified using commercially available assay kits. Acetylcholinesterase and butyrylcholinesterase activities were measured using a published biochemical assay. Results: Acetylcholine levels are significantly elevated in saliva and GCF, whereas GCF levels of butyrylcholinesterase activity are significantly decreased, in patients with periodontal diseases. Acetylcholine levels in saliva and GCF correlated positively with clinical markers of disease severity and with increased levels of IL‐17A and IL‐17F. In contrast, butyrylcholinesterase activity levels in GCF showed significant negative correlations with clinical markers of disease severity and IL‐17A and IL‐17F levels. None of the findings were due to smoking. Conclusions: Elevated acetylcholine levels and reduced butyrylcholinesterase activity are clinically associated with periodontal diseases and elevated levels of IL‐17A and IL‐17F. Therefore, non‐neuronal cholinergic mechanisms may influence IL‐17 biology and the aetiopathogenesis of periodontal diseases and therefore are possible therapeutic targets.